(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article is intended to review the main functions of the essay genre. Paradoxism in the article is an important feature of the essay genre, a constructive method used by the author in creating a journalistic work, and at the same time a complex process of forming a unique, non-trivial view of the world, аlso, the starting point of reflected thought is often an aphoristic, vivid statement or paradoxical definition, which is considered literally contradictory, at first glance, incontrovertible, but mutually exclusive statements, characteristics and theses. Paradox, in scientific terms, (from the Greek paradoxos – “unexpected”) is defined as a formal logical contradiction that arises when two mutually exclusive, opposite opinions turn out to be equally evident. Essay genre is most characteristic of philosophical and ironic genre. A philosophical type of paradox involves a high percentage of intertextual connections, comparisons, contrasts, and timeless themes capable of generating additional meanings.